Morphological and microstructural evolution of PbSe films grown on thermally oxidized Si (111) substrates by chemical bath deposition - Suh, Youngjoon; Suh, Sang-Hee; Lee, Soo Yeon; Kim, Gyeung-Ho (ELSEVIER SCIENCE SA, 2017)
Morphological and microstructural evolution of the PbSe films on the thermally oxidized Si (111) substrates during chemical bath deposition was studied by SEM, XRD and TEM. At the very early stage of deposition, sub-micron scale hemispherical particles are formed on the substrate and they grow with deposition time. The hemispherical particles consist of PbSe, PbSeO4, and PbO2 nanocrystals. Soon after appearance of hemispherical particles, small single crystalline PbSe cuboid particles begin to form mostly on the hemispherical particles and grow with deposition time. At the end of deposition, hemispherical particles are completely replaced by cuboid particles. The cluster mechanism seems to be working at the early stage of deposition, while the ion-by-ion mechanism dominates at the later stage of deposition. The classical heterogeneous nucleation theory is also needed to explain why hemispherical particles are nucleated in the initial stage, and cuboid particles are formed in the later stage of deposition. (c) 2017 Elsevier B.V. All rights reserved.
Keywords: THIN-FILMS; SEMICONDUCTOR-FILMS; LEAD SELENIDE; GAAS(100); MECHANISM; EPITAXY